Intent-Aware Enterprise Architecture Using Persistent AI Agents for Dynamic FinTech Service Composition - Nithesh Gudipuri (The Eastasouth Journal of Information System and Computer Science, 2024)
As financial technology (FinTech) ecosystems grow increasingly complex, the rigidity of traditional service-focused enterprise architectures (EA) becomes a problem in the face of changing customer intent, diverse data sources and shifting regulatory requirements. This paper gathers insights from twenty-one peer-reviewed publications over the last 14 years (2009 to 2022) and suggests an intent-aware enterprise architecture in which the persistent artificial intelligence (AI) agents continuously interpret the organizational and customer intent to orchestrate dynamic FinTech service composition. From the reviewed literature, 52.4 percent covered the use of artificial intelligence and machine learning in financial services, 38.1 percent covered the coordination of multi-agent system (MAS), and 9.5 percent covered service-oriented enterprise architecture and integration with distributed ledger. The study builds on these three streams, with a five-layer architecture: intent interpretation, persistent agent orchestration, dynamic service composition, domain services, and governance. The synthesis suggests that the explanation of these agents, which are persistent, can be used to increase the flexibility and auditability in coordination compared to traditional service-oriented designs, but also imposes new governance and security requirements. The proposed framework provides the FinTech enterprises with structured guidance on delivering adaptive and intent-driven services and supplies a researchers' framework for empirical testing and validation of the proposed framework.